Habitat Characteristics and Morphology of Chlorophyta (Order Bryopsidales) on the Intertidal of Pandanan Hamlet, West Sekotong - Destikawati, Destikawati; Jefri, Edwin; Buhari, Nurliah (Jurnal Biologi Tropis, 2024)
Bryopsidales order macroalgae can be found on various substrates in marine waters. The Bryopsidales order has a morphological form that is shaped like a filament or shaped like a leaf and has pigments like land plants. The study aims to determine the habitat characteristics and morphology of the Bryopsidales order on the coast of Pandanan Hamlet. Sampling was carried out using the line transect method and 1x1 meter quadrant. A total of 5 transect lines were stretched from the shoreline to the point where macroalgae were found. Each transect is placed in quadrants every 20 meters in a zigzag manner. The Bryopsidales order found consisted of 13 species, 3 families and 4 genera growing in habitats with substrates of loamy sand, loam, sand, and sandy loam, rock, dead coral, coral fragments, and live coral. There are 3 types of holdfast were found, namely bulbous, fibrous, and sprawling growers. There are also three blade shapes in this order, namely creeping blades in the Caulerpaceae family, segmented blades in the Halimedaceae family, and blades that are neither creeping nor segmented that resemble sponges in the Codiaceae family.